2010
DOI: 10.1111/j.1742-464x.2010.07672.x
|View full text |Cite
|
Sign up to set email alerts
|

NMR solution structure and function of the C-terminal domain of eukaryotic class 1 polypeptide chain release factor

Abstract: Keywords human eukaryotic class 1 polypeptide chain release factor (eRF1); NMR structure and dynamics; stop codon recognition specificity; termination of protein synthesis Termination of translation in eukaryotes is triggered by two polypeptide chain release factors, eukaryotic class 1 polypeptide chain release factor (eRF1) and eukaryotic class 2 polypeptide chain release factor 3. eRF1 is a three-domain protein that interacts with eukaryotic class 2 polypeptide chain release factor 3 via its C-terminal domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…For an interpretation in molecular terms, we docked our previous cryo-EM based homology model of the human 80S ribosome (Budkevich et al, 2014), which was generated on the basis of S. cerevisiae 80S (Ben-Shem et al, 2011) and T. thermophila 40S and 60S X-ray structures (Klinge et al, 2011; Rabl et al, 2011). eRF3 was modeled based on the homology with its archaeal eEF1A ortholog (aEF1α) from the aEF1α/aRF1 complex (Kobayashi et al, 2012) and eRF1 by docking individual domains of the human factor (Mantsyzov et al, 2010; Song et al, 2000) into the cryo-EM density. The CrPV-STOP IRES has been modeled based on the previously published X-ray structure for domain 3 (Zhu et al, 2011) and cryo-EM model for domains 1 and 2 (Schüler et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For an interpretation in molecular terms, we docked our previous cryo-EM based homology model of the human 80S ribosome (Budkevich et al, 2014), which was generated on the basis of S. cerevisiae 80S (Ben-Shem et al, 2011) and T. thermophila 40S and 60S X-ray structures (Klinge et al, 2011; Rabl et al, 2011). eRF3 was modeled based on the homology with its archaeal eEF1A ortholog (aEF1α) from the aEF1α/aRF1 complex (Kobayashi et al, 2012) and eRF1 by docking individual domains of the human factor (Mantsyzov et al, 2010; Song et al, 2000) into the cryo-EM density. The CrPV-STOP IRES has been modeled based on the previously published X-ray structure for domain 3 (Zhu et al, 2011) and cryo-EM model for domains 1 and 2 (Schüler et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The eS31 interaction seems to be unique for eRF1, as it could not be observed for Dom34 in the Dom34/Hbs1-complex (Becker et al, 2011) or A/T tRNA in the decoding complex (Budkevich et al, 2014) because both are lacking a similar domain. Mutational analysis indicated that the mini-domain influences the specificity of eRF1 for certain stop codons during stop-codon recognition (Mantsyzov et al, 2010), which may explain its exclusive presence in eRF1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The X-ray structure of this region has been left unsolved in the structure of apo-eRF1 as well as in structures of complexes with eRF3, due to the flexibility of this domain. The NMR solution structure of domain C was solved and the extra domain, termed the ‘mini-domain’, was reported to affect codon-specificity (52). According to the latest docking model-assisted cryo-EM study (30), three mutations (E285K, D389G and G394S) identified in this study are located in this ‘mini-domain’, which interacts with the ‘40S beak’, a structural protrusion of the 40S ribosomal subunit that is close to the entry site for translation factors, while the other domain C mutations probably interact with eRF3 or the P-stalk of the large 60S subunit.…”
Section: Discussionmentioning
confidence: 99%
“…The rigid core of domain C contains a flexible insertion forming a mini-domain (8). Domain N is involved in stop codon recognition.…”
Section: Introductionmentioning
confidence: 99%